Pengaruh Kadar Selulosa Pelepah Sawit Terhadap Sifat Dan Morfologi Wood Plastic Composite (WPC) - Yusnila Halawa; Bahruddin Bahruddin; Irdoni Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Cellulose is one of components that contained in palm frond fibers. Cellulose is a polymer which has a molecular average weight, polydispersity and has a long chain that is used as supporting material in manufacturing Wood Plastic Composite (WPC). The purpose of this research is to determine the effect of palm midrib cellulose content to the properties and morphology of WPC. WPC samples prepared by the method of melt blending the fibers of palm midrib (SPS), polypropylene (PP), Maleated polypropylene (MAPP), and paraffin for 1 hour at a temperature of 170 ° C and a rotor speed of 80 rpm using the Internal Mixer. The size of the palm frond fibers used are 40 mesh with the composition of the SPS / PP is 50/50 and 30/70. While the ratio comparison MAPP / cellulose is 0%, 2% and 5% and the cellulose of 41.86%, 52.86% and 56.24%. The test includes testing of the mechanical properties are tensile strength and flexural strength, while physical properties include density, moisture content, water absorption and thickness swelling. Test of morphology using a scanning electron microscopy. The test results showed that the best mechanical properties resulting in a ratio SPS / PP 50/50, cellulose MAPP 0% and 56.24%, with a tensile strength of 10.1 MPa and 27.0 MPa flexural strength. While the physical properties testing are the highest density of 1.511 gr/cm3, best absorption at 0.05%, the water content of 0.01% and a thickness swelling of 0.05%.Keywords: maleated polypropylene, morphology, polypropylene, cellulose, wood plastic composite